Anthony Asquith's The importance of being earnest - Wilde, Oscar 1854-1900; Frankel, Benjamin 1906-1973 (<<The>> Criterion Coll., 2002)
A lovestruck suitor is put off when his fiancee announces she can only love a man named Earnest.
1.33:1 aspect ratio. - New, restored high-definition digital transfer
Orig.: Großbritannien 1952
Enth. rare production stills with notes by film historian Bruce Eder
Keywords: Comedy films; DVDs; Feature films